The Effects of Hearing Loss on Fast Oral Motor Skills, Speed of Speech and Intelligibility of Speech - Mohammad Sadegh Seif-Panahi; Zahra Soleymani; Mohammad Rahim Shahbodaghi; Amir Shiani; Tahmineh Soleymani (University of Social Welfare and Rehabilitation Sciences, 2007)
Objective: The negative effects of hearing loss rendered to the processes of fast motor skills of articulators, speed and intelligibility of speech have been proved scientifically. The main question is how different thresholds are, can effect in such and try to find relations between mentioned three speech skills specially if there are relations between tests in evaluating speed articulators such as oral diadochokinesis and speed of speech. Materials & Methods: This cross-sectional-analyzical study was performed on 46 hearing-impaired (profound, sever, moderately sever) and 15 normal -hearing high-school students that were selected randomized. Subjects were measured by oral diadochokinesis test (The records were analyzed by speech analyzer of Dr. Speech Software), 100 words text to evaluate speed of speech according read words per minute), and use of rate scale method to define the rate of intelligibility of speech in reading text. Data were analyzed by SPSS software. Results: The general pattern suggest that the high threshold hearing subjects spend more time to repeat oral diadochokinesis syllables and have decreased speed and intelligibility of speech. In respect to speed of speech and oral diadochokinesis ability, there were only significant differences between profound hearing-impaired subjects and both sever and moderately sever subjects (P0/05). General findings suggest some significant relationship between intelligibility and speed of speech (P>0.05). Conclusion: Respect to the negative effects of hearing loss on fast oral motor skills, speed of speech and intelligibility of speech and such relationships between these three variables, suggested interventions on each of the above variables may be useful in other comparative subjects.